The Impact of Different Forms of Advertisements on User Behavior: A Study Based on Audience Feedback on Chinese Streaming Platforms - Chen Qingyang (SHS Web of Conferences)
With the continuous development of the Internet and social media platforms, the changes in advertising communication methods have not only altered the presentation of advertisements but also profoundly influenced consumer behavioral feedback. In order to more effectively capture the attention of the target audience and enhance the effectiveness of advertising, it has become important to study the relationship between advertising formats and consumer feedback. This study utilizes questionnaire surveys and semi-structured interviews to explore the impact and relationship between advertising and consumer behavior through data analysis. The study indicated that different advertisements have varying effectiveness across three dimensions of advertising communication, and broadcast advertising unexpectedly presented a surprising result and discovery in this process. Furthermore, the cultural background of the audience is a significant factor in the dimensions of the audience, affecting the dissemination and effectiveness of advertising. This sheds light for businesses and advertising decision-makers on the influence mechanisms of different advertising formats on consumer cognition, attitudes, and behaviors, providing new empirical support for relevant theories.